2017
DOI: 10.1038/s41522-017-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and comparison of bacterial communities on reverse osmosis membranes of a full-scale desalination plant by bacterial 16S rRNA gene metabarcoding

Abstract: Microbiomes of full-scale seawater reverse osmosis membranes are complex and subject to variation within and between membrane units. The pre-existing bacterial communities of unused membranes before operation have been largely ignored in biofouling studies. This study is novel as unused membranes were used as a critical benchmark for comparison. Fouled seawater reverse osmosis membrane biofilm communities from an array of autopsied membrane samples, following a 7-year operational life-span in a full-scale desa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 51 publications
6
24
0
Order By: Relevance
“…On day 3, corresponding with the average startup time of EDC+WW reactors, the only OTU that became differentially abundant in EDC+WW relative to the control planktonic communities belonged to Sphingobacteriia . This finding is consistent with the functional role attributed to Flavobacteriia and Sphingobacteriia , both of which were found to represent key members in the formation and functioning of biofilms in diverse environments (Battin et al, 2016; Nagaraj et al, 2017; Pollet et al, 2018), probably due to their ability to degrade diverse complex organic material and their superior attachment ability. Furthermore, Sphingobacteriia were previously reported in bioelectrochemical devices both at the plankton fraction and anodic biofilm as homoacetogens or fermenters of complex organic substances that support electrogenic species within the biofilm through syntrophic interactions (Gao et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…On day 3, corresponding with the average startup time of EDC+WW reactors, the only OTU that became differentially abundant in EDC+WW relative to the control planktonic communities belonged to Sphingobacteriia . This finding is consistent with the functional role attributed to Flavobacteriia and Sphingobacteriia , both of which were found to represent key members in the formation and functioning of biofilms in diverse environments (Battin et al, 2016; Nagaraj et al, 2017; Pollet et al, 2018), probably due to their ability to degrade diverse complex organic material and their superior attachment ability. Furthermore, Sphingobacteriia were previously reported in bioelectrochemical devices both at the plankton fraction and anodic biofilm as homoacetogens or fermenters of complex organic substances that support electrogenic species within the biofilm through syntrophic interactions (Gao et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Proteobacteria and especially Îłproteobacteria dominated biofilm communities colonizing artificial surfaces in Toulon and Lorient, France (Briand et al, 2017), and in Mauritian coastal waters (Rampadarath et al, 2017). DNA metabarcoding showed that the proportion of Îł-proteobacteria increased and dominated artificial surfaces with cupreous anti-fouling coating treatments (von Ammon et al, 2018).16S rRNA gene metabarcoding showed that proteobacteria dominated bacterial communities in used reverse osmosis membranes in a desalination plant, with β-proteobacteria being found in severely fouled membranes (Nagaraj et al, 2017). However, the community composition and diversity obtained by high throughput DNA sequencing technologies of biofilms is dependent on the DNA extraction method selected (Corcoll et al, 2017).…”
Section: Marine Biofilms Cause Biofoulingmentioning
confidence: 99%
“…They are prevalent on desalination plant membranes (Nagaraj et al . ) and have been associated with rotifer ( Brachionus plicatilis ) culture. Although only identified in small numbers, representatives of denitrifying genera including Comamonas, Brachymonas, Nitrospira , Desulfovibrio , Thiobacillus, Acidovorax, Dechloromonas, Meganema and Hyphomicrobium were also found in all feeding phases.…”
Section: Discussionmentioning
confidence: 99%